The Impact of the Syrian Refugee Crisis on Firm Entry and Performance in Turkey - Akgunduz, Yusuf Emre (World Bank, Washington, DC, 2018)
This study analyses how the Syrian refugee inflows into turkey affected firm entry and performance. To estimate the casual effects, instrumental variables, difference-indifferences and synthetic control methodologies are used. The results suggest that hosting refugees is favourable for firms. Total firm entry does not seem to be significantly affected. However, there is a substantial increase in the number of new foreign-owned firms. In line with the increase in new foreign-owned firms, there is some indication of growth in gross profits and net sales.